Tokens for the foundlings - Curtis, Tony 1955- (Seren, 2012)
This collection of poetry is divided into three sections: orphans and foundlings, infancy, and early childhood, and includes poems contributed by Carol Ann Duffy, Seamus Heaney, Gillian Clarke, and Stephen Knight